An Acoustic Analysis of consonants of Khattak Dialect of Pashto - Rehmat, Javeria (Journal of Applied Linguistics, 2025)
Pashto, an ancient language written in Perso-Arabic script, is predominantly spoken in Pakistan's Khyber Pakhtunkhwa Province and Afghanistan. Despite its wide usage, more research is needed on the consonantal sounds of the Khattak dialect. This study aims to fill this gap by providing a detailed acoustic analysis of the Khattak dialect's consonants. An inventory of 28 consonant phonemes was developed using the standard Pashto IPA chart and the Yusufzai dialect chart. Minimal pairs were created and recorded using an Android phone and an iPhone, involving two native speakers, one male and one female, both BS students. The recordings were converted into .wav files, and acoustic analysis was performed using PRAAT software, focusing on formants and waveforms. The findings offer comprehensive insights into the phonetic characteristics of the Khattak dialect, contributing to a broader understanding of Pashto phonology and addressing a significant gap in the literature on Pashto dialectology. This research not only provides a foundational inventory for future studies but also enhances the comparative linguistic analysis of Pashto dialects. It underscores the unique phonetic features of the Khattak dialect, facilitating its preservation and further linguistic exploration. The study's methodology, involving high-quality recordings and native speakers, ensures the reliability and authenticity of the data, providing a valuable reference for linguistic research and applications in speech technology. Keywords : Acoustic; Khattak; dialect; Pushto; consonant